Gliomas with intratumoral abscess formation: Description of new cases, review of the literature, and the role of 99mTC‐Leukoscan. Issue 7 (30th May 2015) - Campennì, Alfredo; Caruso, Gerardo; Barresi, Valeria; Pino, Mariangela; Cucinotta, Mariapaola; Baldari, Sergio; Caffo, Maria
Abstract: Abscess formation within a brain tumor is uncommon. Intrasellar or parasellar tumors are the most common neoplasms that develop such complications. Cerebral gliomas with abscesses are extremely rare. In this paper three rare cases of glioma associated with abscess formation are described. The diagnosis of brain tumor associated with abscess is particularly difficult by conventional neuroradiological studies. 99m Tc‐labeled sulesomab can be useful in the diagnosis of brain tumors with intratumoral abscesses. There are no precise guidelines for the diagnosis and treatment of cerebral gliomas associated with abscesses formation for the low number of cases reported to date. Appropriate treatment, aimed at radical surgery, and a suitable antibiotic‐protocol, deferring adjuvant postoperative therapy, is associated with a more favorable outcome. A review of the pertinent literature is also performed.